2013
DOI: 10.1021/ed200809a
|View full text |Cite
|
Sign up to set email alerts
|

Concept Learning versus Problem Solving: Evaluating a Threat to the Validity of a Particulate Gas Law Question

Abstract: Three different samples of students were asked to answer five multiple-choice questions concerning the properties of a sample of helium gas (particle speed, state of matter, sample volume, sample pressure, and particle distribution), including a particulate question first used by Nurrenbern and Pickering (particle distribution). In the first experiment, half of the students were given the boiling point of helium under these conditions while the other half were not; in the second experiment, half of the student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Also, the presence of difficult, new and/ or low frequency words within the text is associated with longer gaze durations and leads to longer total inspection times (Sereno and Rayner, 2003;Smallwood et al, 2008;Foulsham et al, 2013), contributing to a slower reading pace (Foulsham et al, 2013) and worse reading comprehension (Smallwood et al, 2008). They are more abstract (Gericke and Hagberg, 2007;Al-Balushi, 2011, 2013bAl-Balushi and Coll, 2013;Taber, 2013), less frequently encountered by learners than macroscopic description of natural phenomena and they represent more difficult concepts than macroscopic words (Sanger et al, 2013;Kelly, 2014;Milenković et al, 2014;Prilliman, 2014;Ryan and Herrington, 2014;Sjöström and Talanquer, 2014;Warfa et al, 2014). They are more abstract (Gericke and Hagberg, 2007;Al-Balushi, 2011, 2013bAl-Balushi and Coll, 2013;Taber, 2013), less frequently encountered by learners than macroscopic description of natural phenomena and they represent more difficult concepts than macroscopic words (Sanger et al, 2013;Kelly, 2014;Milenković et al, 2014;Prilliman, 2014;Ryan and Herrington, 2014;Sjöström and Talanquer, 2014;Warfa et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the presence of difficult, new and/ or low frequency words within the text is associated with longer gaze durations and leads to longer total inspection times (Sereno and Rayner, 2003;Smallwood et al, 2008;Foulsham et al, 2013), contributing to a slower reading pace (Foulsham et al, 2013) and worse reading comprehension (Smallwood et al, 2008). They are more abstract (Gericke and Hagberg, 2007;Al-Balushi, 2011, 2013bAl-Balushi and Coll, 2013;Taber, 2013), less frequently encountered by learners than macroscopic description of natural phenomena and they represent more difficult concepts than macroscopic words (Sanger et al, 2013;Kelly, 2014;Milenković et al, 2014;Prilliman, 2014;Ryan and Herrington, 2014;Sjöström and Talanquer, 2014;Warfa et al, 2014). They are more abstract (Gericke and Hagberg, 2007;Al-Balushi, 2011, 2013bAl-Balushi and Coll, 2013;Taber, 2013), less frequently encountered by learners than macroscopic description of natural phenomena and they represent more difficult concepts than macroscopic words (Sanger et al, 2013;Kelly, 2014;Milenković et al, 2014;Prilliman, 2014;Ryan and Herrington, 2014;Sjöström and Talanquer, 2014;Warfa et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The three levels included in this triplet nature of chemistry are considered as levels of thought (Johnstone, 2000). Much of the difficulty students have in learning chemistry and the related misconceptions have been considered to be a result of their inability to comprehend the details of the phenomenon undertaken at the three levels and their failure to move spontaneously among them (Sanger et al, 2013;Kelly, 2014;Milenković et al, 2014;Prilliman, 2014;Ryan and Herrington, 2014;Sjöström and Talanquer, 2014;Warfa et al, 2014). Much of the difficulty students have in learning chemistry and the related misconceptions have been considered to be a result of their inability to comprehend the details of the phenomenon undertaken at the three levels and their failure to move spontaneously among them (Sanger et al, 2013;Kelly, 2014;Milenković et al, 2014;Prilliman, 2014;Ryan and Herrington, 2014;Sjöström and Talanquer, 2014;Warfa et al, 2014).…”
Section: Cognitive Processing Of Macroscopic and Submicroscopic Levelmentioning
confidence: 99%
“…At the first sight of their encounters with important chemistry terminologies, college students would often feel puzzled for individual difficulties in solving abstract or complicated problems, such as gas chemistry (Sanger et al, 2013), electrochemistry (Cheung, 2011), stoichiometry (Davidowitz et al;2010Sanger, 2005, chemical equilibrium (Cheung et al, 2009) and stereochemistry (Abraham et al, 2010). Scholars attributed students' pri-Scholars attributed students' pri-students' pri-students' pri-tudents' primary dilemma of chemistry learning to their lack of authentic access for integrating cognitive skills with their fundamental understanding of chemistry concepts (Sanger, 2005;St Clair-Thompson et al, 2012).…”
Section: Dilemma Of Chemistry Learningmentioning
confidence: 99%
“…In the educational perspective of strategic PSS applications, Salt and Tzougraki (2011) demonstrated that though students could have solved algorithmic-type chemistry problems, they still had difficulty answering conceptual-type problems on the same topics, especially if these conceptual problems were given in detailed description of the particulate nature level (also Özmen, 2013). To look for more cognitional features of conceptual changes, researchers emphasized that students had to integrate clear conceptions with strategic PSS applications for individual learning (Pickering, 1990;Cracolice et al, 2008;Sanger et al, 2013), to avoid students' inability to answer algorithmic versus particulate conceptual questions during the initiated process of chemistry reasoning skills.…”
Section: Dilemma Of Chemistry Learningmentioning
confidence: 99%
See 1 more Smart Citation